2013
DOI: 10.1002/vnl.21312
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study on short-term dielectric breakdown of poly(vinyl chloride)

Abstract: This paper reports the breakdown voltage of plasticized poly(vinyl chloride) under AC and DC electric fields. The effect of ramp rate on breakdown voltage was investigated. A statistical analysis of breakdown data was carried out by using the two‐parameter Weibull distribution. The best linear fit was determined by an estimation based on the method of maximum likelihood. The 90% confidence intervals of Weibull plots were calculated, and the model was validated by the χ2 test. The study showed that the shape pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Gockenbach and Schiller [22] found that the highest breakdown voltage of XLPE was measured at DC voltage with negative polarity and the lowest at AC voltage. In previous works, we pointed out that breakdown voltage of polyesterimide, polyamide imide and polyvinyl chloride depends on the shape of applied electrical field [23,24]. Iddrissu et al [25] reported that under DC stress, the initiation and growth of electrical trees are dependent on the polarity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gockenbach and Schiller [22] found that the highest breakdown voltage of XLPE was measured at DC voltage with negative polarity and the lowest at AC voltage. In previous works, we pointed out that breakdown voltage of polyesterimide, polyamide imide and polyvinyl chloride depends on the shape of applied electrical field [23,24]. Iddrissu et al [25] reported that under DC stress, the initiation and growth of electrical trees are dependent on the polarity.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is allotted to the different amounts of the space charge accumulated under the two polarities. It was indicated effect of the form of applied voltage on dielectric breakdown [22][23][24][25]. Gockenbach and Schiller [22] found that the highest breakdown voltage of XLPE was measured at DC voltage with negative polarity and the lowest at AC voltage.…”
Section: Discussionmentioning
confidence: 99%